Acute alcohol intoxication and suicide: a gender-stratified analysis of the National Violent Death Reporting System. Issue 1 (24th May 2012) - Kaplan, Mark S; McFarland, Bentson H; Huguet, Nathalie; Conner, Kenneth; Caetano, Raul; Giesbrecht, Norman; Nolte, Kurt B
Abstract : Objectives: Although it is well known that people with alcohol dependence are at a markedly elevated risk for suicide, much less is known about the role of acute alcohol use in suicidal behaviours. The primary aims of this epidemiological study were to assess the prevalence and factors associated with acute alcohol intoxication among 57 813 suicide decedents in 16 states. Methods: Data from the restricted National Violent Death Reporting System 2003–2009 for male and female suicide decedents aged 18 years and older were analysed by multiple logistic regression to compare decedents with and without acute alcohol intoxication (defined as blood alcohol concentration (BAC) ≥0.08 g/dl). Results: Among men, those who were younger, American Indian/Alaska Native, Hispanic, veterans, of lower educational attainment, deceased from a self-inflicted firearm injury or hanging/suffocation and residing in rural areas were more likely to have been intoxicated at the time of death. Among women, the factors associated with a BAC ≥0.08 g/dl were younger age, being American Indian/Alaska Native, and using a firearm, hanging/suffocation or falling as method of death. Conclusions: In both men and women, alcohol intoxication was associated with violent methods of suicide and declined markedly with age, suggesting that addressing risks associated with acute alcohol use may be of the greatest aid in the prevention of violent suicides among young and middle age adults.